2017
DOI: 10.1017/hpl.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced microstructures on silicon for laser-driven acceleration experiments

Abstract: Ultrashort laser pulses are used to create surface structures on thin (25 µm) silicon (Si) wafers. Scanning the wafer with a galvanometric mirror system creates large homogeneously structured areas. The variety of structure shapes that can be generated with this method is exemplified by the analysis of shape, height and distance of structures created in the ambient media air and isopropanol. A study of the correlation between structure height and remaining wafer thickness is presented. The comparatively easy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…An automated, 0.5 Hz nano-foil target positioning system for intense laser plasma experiments [11] 9. Laser-induced microstructures on silicon for laserdriven acceleration experiments [14] 10. Developing targets for radiation transport experiments at the Omega laser facility [15] 11.…”
Section: Special Issue Contentmentioning
confidence: 99%
See 3 more Smart Citations
“…An automated, 0.5 Hz nano-foil target positioning system for intense laser plasma experiments [11] 9. Laser-induced microstructures on silicon for laserdriven acceleration experiments [14] 10. Developing targets for radiation transport experiments at the Omega laser facility [15] 11.…”
Section: Special Issue Contentmentioning
confidence: 99%
“…Submissions for the special issue covered the invited topics and also branched out into broader areas and capabilities. Papers described research on: techniques for the production of targets for inertial confinement fusion (ICF) [1][2][3][4][5][6][7][8] , micro-assembly [3,8,9] , liquid targets [10] , systems for delivery of targets at high repetition rates [5,11,12] , fundamental target fabrication processes [2,4,[13][14][15][16] , low density materials [15,17,18] and metrology methods [7,18,19] . In addition, there were three important review papers [1,5,12] that give an excellent snapshot of the current capabilities across the world.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Self-focusing of the subsequent pulses deepens these so-called ripples, eventually resulting in cone-shaped microstructures. Further studies have shown that the size and form of these structures can be adjusted without much effort by changing the laser and processing parameters [12][13][14][15] . This technique is well studied for silicon, but also works with other materials such as titanium or aluminium [16] .…”
Section: Introductionmentioning
confidence: 99%